An ISM Modeling for The Innovation Barrier in Processed Food Industry - Ernawati, Erni; Machfud; Fahmi, Idqan; Djohar, Setiadi (School of Business, Bogor Agricultural University (SB-IPB), 2022)
In Indonesia, the processed food industry is one of the strategic sectors of economic growth because rapid and massive innovation expected to accelerate the recovery of the Indonesian economy during Covid-19 pandemic. Therefore, this study aims to identify the innovation barriers as well as to understand how they interact with each other so that the decision makers can focus on to overcome these barriers. There is a presentation of hierarchy-based and the mutual relationships among these hindrances using interpretive structural modeling. Three main barriers including economic or political uncertainty, overlapping government regulations, and low organizational commitment was identified to show a high driving power with a low dependence because they have strategic importance and require great attention from stakeholders. The results become a reference for stakeholders in formulating the innovation development strategies and several formulating policies for the maintenance of political or economic stability as well as the harmonization of regulations. Keywords: barriers, innovation, ISM, modeling, processed food industry